The Histological Structure and Enzyme Activities in the Digestive System of Octopus sinensis - Xuemei LI; Xingqiang WANG; Siqing CHEN; Fenghui LI; Qing CHANG; Baocheng DANG; Shouyong WEI; Li BIAN (Progress in Fishery Sciences, 2023)
The East Asian common octopus (Octopus sinensis), is mainly distributed along the southeast coast of China. It has become an important aquaculture species in the coastal areas of the Fujian and Guangdong province due to its excellent culture features such as high conversion rate, fast growth rate, large size, and high market price. The main culturing methods of O. sinensis are industrialized, indoor, and cage culturing. The density is high during cage culturing. If the feed is insufficient or the feeding interval too long, there are attacks and cannibalism among individuals, which adversely impacts the culturing income. Therefore we urgently need to undertake digestive physiology research to explore the digestive functions of O. sinensis. This research will provide valuable information to identify an appropriate feeding frequency and reduce the economic loss caused by cannibalism. At present, there is no relevant research on the digestive physiology of O. sinensis. In this study, the histological structure of each digestive organ of O. sinensis was observed to explore the relationship between the tissue structure and digestive function. We investigated the trypsin, amylase, and lipase activities in the anterior salivary gland, posterior salivary gland, crop, digestive gland, stomach, cecum, and intestine before and after feeding. The changes in plasma glucose, plasma triglyceride, plasma total cholesterol, plasma total protein and muscle glycogen before and after feeding were analyzed to determine the digestion and absorption duration in O. sinensis.O. sinensis is an aggressive carnivore with a highly developed digestive system. The histological results showed that the crop, stomach, cecum, and intestine of O. sinensis is composed of three layers, the mucosal, submucosal, and muscular, and the inner wall contained many folds. Both the anterior and posterior salivary glands were compound tubular glands, which were composed of oval and circular gland tubes with many secretory ducts. The crop widens and expands from the esophagus into a large lumen, and the cuticle of the mucosal layer was thin (with a thickness of approximately 2.57–5.44 μm). The stomach was spherical, the gastric cavity was biased to one side, and the inner wall contained many folds. The muscular layer of the gastric wall was the most developed layer with the cuticle approximately 99.97–383.82 μm. The cecum was double helix and the inner wall contained rich long folds and secondary folds. The submucosa at the free end of some of the long lateral folds contained some mucous glands, and the mucosal layer without any cuticle. The digestive gland was the largest proportion of the digestive system and was composed of hepatic lobules. The boundary of the hepatic lobules was difficult to distinguish. The diameter of the intestine was approximately 2.50 mm, the tube wall was thin and the mucosal layer had no cuticle. The intestinal mucosa forms wavy longitudinal folds in the mucosa, including a pair of longer folds, which occupied almost the entire intestine. The analysis of the digestive enzyme activities and nutrient metabolism showed that trypsin activity was significantly higher than that of lipase and amylase. The trypsin activity in the digestive gland reached (148.74±21.25) U/mg, and the amylase activity in the digestive gland and stomach reached (3.68±0.59) U/mg and (2.48±0.64) U/mg, respectively. The lipase activities did not vary between the different tissues. After feeding, the plasma total protein concentration reached the lowest levels of (161.50±67.51) mg/mL at 120 min, and then increased. The plasma glucose and muscle glycogen concentrations of O. sinensis reached maximums of (1.54±0.44) mmol/L and (4.75± 0.13) mg/g at 200 min, respectively. Feeding had little effect on the plasma lipid concentration in O. sinensis, the plasma cholesterol concentration did not vary significantly while feeding (P < 0.05), and there was limited variation in the plasma triglyceride concentration. The digestion process was divided into two stages. The first stage occurs in 0~60 min as food entered the crop and stomach, and the digestive gland secreted large doses of trypsin. Initially, the trypsin in the stomach mixed with the food, resulting in decreased trypsin activity. At this stage, only small amounts of nutrients are absorbed and the body needs to consume nutrients to supply energy for the digestion process. Therefore, a decrease in plasma glucose, plasma protein, and muscle glycogen content occurred. The second stage occurs in 120~300 min and involves high trypsin activity. In the progress of extracellular digestion and intracellular digestion, the trypsin activity of various digestive organs decreased gradually, and nutrients increased gradually. At 400 min, the trypsin activity, plasma glucose, plasma protein, and muscle glycogen returned to the pre-feeding levels, indicating the end of the digestion and absorption process. The whole digestion and absorption process of O. sinensis lasted approximately 400 min. Therefore, the appropriate feeding interval for O. sinensis culture is 6~7 h.